Richness distribution patterns of marine elasmobranchs in Colombia - Ágreda-Arango, Jose; Ballesteros, Carlos; Bessudo, Sandra; Bent-Hooker, Heins; Bolaños, Nacor; Caldas, Juan Pablo; Duarte, Luis Orlando; Gómez, Fabio; Lara, Gustavo; Loaiza, Jhonatan; et al. (Revista de Biología Marina y Oceanografía, 2022)
An analysis on the species richness distribution of marine sharks and batoids for the Colombian Caribbean and Pacific regions was carried out. A total of 138 species was documented in nearby marine waters off Colombia, including 76 sharks and 62 batoids; 20 species occurred on both coasts with the Caribbean generally having a higher observed richness than the Pacific. The Caribbean had high richness values both in the insular as well as in the northern region. However, the highest richness values per spatial unit in the Pacific islands of Gorgona and Malpelo, with completeness richness estimate represented mostly by values below 90%. Richness estimators showed values higher than the observed richness, indicating that the inventories and the description of marine shark and batoid richness in Colombia are still incomplete. Despite this, the results of this study are relevant to make decisions aimed at the conservation of this taxonomic group, both in marine protected and unprotected areas of the Pacific and Caribbean coasts of Colombia